The Inventive Activity in Biodiesel Production - Angulo-Cuentas, Gerardo; Cadena-Wilches, Luz; Nuñez-Mejia, Elvis (Recent Patents on Engineering, 2019)
Background: Biodiesel is an energy source considered of great importance in both production processes and to satisfy domestic needs. However, production and use of this biofuel have troubles regarding the sustainability and efficiency. Objective: Considering the problems in the production of a sustainable and efficient biodiesel carrie, this study of patents analysis was done having the main objective to identify new technologies related to biodiesel production and the solution to these problems. Methodology: For the study, a methodology was implemented that allowed the analysis of patents related to biodiesel production published between 2010 and 2016. The stages of the methodology include: search in the patent database; analysis of the technological development at the global level, and identification and description of technological trends. Results: The search resulted in 1053 patent’s applications. Among the results, technology indicators are described such as the life cycle of the technology, leading applicants, industrial impact index, technological variability, among others. Conclusion: The results show information related to technologies that can be useful for biodiesel industry since technological fields granting solutions to the inconvenient respecting the production of this biofuel were identified. Technological trends found are focused on extracting useful products for biodiesel industry through production, genetic mutation, growing and processing of oleaginous microorganisms.
Keywords: biofuel